The acceptability and feasibility of emailed parent questionnaires for medical and developmental surveillance after NICU discharge. (April 2018) - Litt, Jonathan; Agni, Meghana; Jacobi-Polishook, Talia; Melvin, Patrice; McCormick, Marie; Stewart, Jane; Belfort, Mandy
Abstract Objectives The following are the objectives of this study: (1) Assess the feasibility and acceptability of emailing parent-reported measures of infant health and development after NICU discharge. (2) Examine whether post-discharge questionnaire data helps identify infants most likely to benefit from specialized follow-up care. Study design Parents of 51 infants <32 weeks' gestation received email questionnaires at 44 weeks postmenstrual age (PMA) and 6 months corrected age (CA). Adverse infant outcomes were assessed in-person at 6 months: (1) Bayley-III cognitive or motor score <85; (2) weight, length, or head circumference <10th percentile; (3) new referral for medical or developmental services. Results Questionnaire response was 48 (94%) at 44 weeks PMA and 46 (90%) at 6 months CA. 36 (70%) infants were assessed at 6 months; 72% had at least 1 adverse outcome. Poorer transition home, feeding problems, and special health care needs at 44 weeks PMA predicted adverse outcomes. Feeding problems, maternal depression, and lower infant health-related quality of life at 6 months CA correlated with adverse outcomes. Conclusions Emailed questionnaires after NICU discharge were feasible to implement and acceptable to families. Repeated post-discharge assessments may help identify infants at heightened health and developmental risk.